Treatment outcome of pediatric tuberculosis in eastern Ethiopia - Weldegebreal, Fitsum; Teklemariam, Zelalem; Mitiku, Habtamu; Tesfaye, Tamrat; Abrham Roba, Aklilu; Tebeje, Fikru; Asfaw, Abiyot; Naganuri, Mahantash; Jinnappa Geddugol, Bahubali; Mesfin, Frehiwot; Abdulahi, Ibsa Mussa; Befikadu, Hilina; et al. (Frontiers in Pediatrics, 2022)
Background Children are more vulnerable to developing active Mycobacterium tuberculosis infection which causes significant morbidity and mortality. However, the contribution of childhood tuberculosis and its treatment outcomes have not been well documented, and no research has been conducted in eastern Ethiopia. Objective This study aimed to assess the treatment outcome and its predictors of pediatric tuberculosis in eastern Ethiopia from September 1, 2017 to January 30, 2018. Methods A retrospective study was conducted in eight selected hospitals in eastern Ethiopia. Data on 2002 children with tuberculosis was extracted by using the standard checklist of the national tuberculosis treatment format. Treatment outcomes were determined according to the standard definitions of the National Tuberculosis and Leprosy Control Programme. Data were entered into Epi Data software version 3.1 and exported to Statistical Package for Social Science (SPSS) version 20 for analysis. Bivariable and multivariable regression analyses were carried out to examine the associations between dependent and independent variables. A P-value of <0.05 was considered statistically significant. Result The overall successful treatment rate was 1,774 (88.6%) [95% confidence interval (CI): (80.59–97.40)]. A total of 125 (6.2%), 1,648 (82.3%), 59 (2.9%), and 19 (0.9%) children with tuberculosis (TB) were cured, completed, defaulted, and died, respectively. A high number of defaulters and deaths were reported in the age group <10 years. More children with smear-positive pulmonary TB (74.4%) were cured, while smear-negative tuberculosis had higher treatment completion rates. Being male in sex (adjusted odds ratio (AOR): 0.71, 95% CI: 0.53, 0.96) and those with human immunodeficiency virus (HIV) positive sero status (AOR: 0.51, 95% CI: 0.29, 0.90) had a lower chance of a successful treatment outcome. Conclusion In this study, thee treatment success rate was higher than the recent World Health Organization report. Those males and HIV seropositive status were less likely to have a successful treatment outcome. Therefore, efforts should be made by each health institution in eastern Ethiopia by giving emphasis on male and HIV-positive individuals.